2016
DOI: 10.1249/mss.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training for Cognitive and Mental Health in Adolescents

Abstract: This study highlights the potential of embedding HIIT within the school day for improving cognitive and mental health among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(187 citation statements)
references
References 42 publications
(32 reference statements)
12
145
2
6
Order By: Relevance
“…The only long term intervention study we are aware of observed moderate ES for the effects of 8-week HIT on executive function assessed by the trail making task [12]. Similarly, we found a moderate positive ES for visual memory and learning in favour of the intervention group.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The only long term intervention study we are aware of observed moderate ES for the effects of 8-week HIT on executive function assessed by the trail making task [12]. Similarly, we found a moderate positive ES for visual memory and learning in favour of the intervention group.…”
Section: Discussionsupporting
confidence: 63%
“…However, the evidence from intervention studies on the effects of PA on cognition in adolescents is limited [11] and a few studies have investigated the impact of HIT on cognition in children or in adolescents. Eight-week HIT had a small positive effect on executive functions measured by the trail making task in adolescents aged 15 years [12]. A single bout…”
Section: Introductionmentioning
confidence: 91%
“…The small sample size of 25 students was a limitation in this study. Costigan, Eather, Plotnikoff, Hillman, and Lubans (2016) evaluated two high-intensity interval training (HIIT) interventions (aerobic or resistance with aerobic, [8-10 minutes sessions, three times a week for 8 weeks]) compared to a control group who engaged with usual school-based physical exercise classes. The effect of the three intervention groups was assessed on well-being, distress, executive function and physical self-concept in 65 young people with a mean age of 16 years.…”
Section: Review Of the Intervention Studiesmentioning
confidence: 99%
“…In the resistance and aerobic group, effect sizes indicated small improvements in well-being and perceived appearance and moderate improvements in executive function. From pre-to post-workout, there was a significant improvement in feeling state scores in the aerobic exercise group, with no changes in the other studied variables (Costigan et al, 2016). Melnyk et al (2013) In a RCT by Wipfli, Landers, Nagoshi, and Ringenbach (2011), undergraduate students with a mean age of 20 years were randomized to either 30 minutes of aerobic group-based exercise or groupbased stretching, three times a week for 7 weeks.…”
Section: Review Of the Intervention Studiesmentioning
confidence: 99%
“…Despite the wide range of benefits, aerobic exercise is usually performed at low and moderate intensity during long training sessions (>30 min), becoming monotonous and only having the effects experienced after several weeks. Thus, in order to optimize these benefits, high intensity interval training (HIIT), consisting of high-intensity exercise bouts interspersed with intervals of passive or active recovery, has recently emerged in the scientific literature as an interesting strategy for improving cardiorespiratory fitness (Allen et al, 2017), health outcomes and cognitive functions (Costigan, Eather, Plotnikoff, Hillman, & Lubans, 2016) compared to continuous moderate exercise. Although this exercise modality has been applied in different clinical populations, little is known about its chronic effects among drug users.…”
Section: Introductionmentioning
confidence: 99%